Bacterial pathogens activate plasminogen to breach tissue barriers and escape from innate immunity. (1st November 2016) - Peetermans, Marijke; Vanassche, Thomas; Liesenborghs, Laurens; Lijnen, Roger H.; Verhamme, Peter
Abstract: Both coagulation and fibrinolysis are tightly connected with the innate immune system. Infection and inflammation cause profound alterations in the otherwise well-controlled balance between coagulation and fibrinolysis. Many pathogenic bacteria directly exploit the host's hemostatic system to increase their virulence. Here, we review the capacity of bacteria to activate plasminogen. The resulting proteolytic activity allows them to breach tissue barriers and evade innate immune defense, thus promoting bacterial spreading. Yersinia pestis, streptococci of group A, C and G and Staphylococcus aureus produce a specific bacterial plasminogen activator. Moreover, surface plasminogen receptors play an established role in pneumococcal, borrelial and group B streptococcal infections. This review summarizes the mechanisms of bacterial activation of host plasminogen and the role of the fibrinolytic system in infections caused by these pathogens.